(untitled) (JournalNX - A Multidisciplinary Peer Reviewed Journal, 2021)
In this paper a very easy process of designing & fabricating Microstrip antenna with adhesive copper tape is presented. The rectangular structure is designed for 700MHz and it is modelled with High Frequency Structure Simulator (HFSS). The prototype is fabricated with FR4 material and 70 micron thick copper tape. The fabricated antenna is tested on Antenna Trainer Kit to observe radiation pattern.